Problematika Pembelajaran di Sekolah Dasar dan Solusi Strategis melalui Inovasi Pembelajaran Berpusat pada Siswa - Dewi Citra Rusyadi; Mila Sari; Syofiani; Rieke Alyusfitri (STKIP Subang, 2026)
Learning in primary schools plays a strategic role in developing students’ cognitive abilities, attitudes, and skills. However, learning practices in primary schools continue to face various challenges, including low levels of student engagement, the dominance of teacher-centered instruction, and the mismatch between instructional strategies and students’ developmental characteristics. These conditions negatively affect the quality of learning processes and outcomes. This article aims to analyze learning-related problems in primary schools and to propose strategic solutions through student-centered learning innovation. This study employs a literature review method with a conceptual analysis approach based on relevant scientific publications, educational policies, and previous research findings. The analysis indicates that student-centered learning innovation serves as a strategic solution to enhance students’ engagement, autonomy, and learning motivation through the implementation of active, contextual, collaborative, and reflective learning approaches. Therefore, student-centered learning innovation functions not merely as an instructional shift but as a strategic effort to improve the quality of learning in primary schools